Something beautiful for God : Mother Teresa of Calcutta - Muggeridge, Malcolm (New York : Harper & Row Publishers, Inc., 1971)
Malcolm Muggeridge interviews Mother Teresa, an Indian nun who through her life and her dedication to rescuing abandoned babies exemplifies, for people of all religious beliefs, the power for good in the individual.
Something beautiful for God -- Mother Teresa's way of love -- Mother Teresa speaks -- A door of utterance
Keywords: TERESA, -- MOTHER, SAINT, -- 1910-1997